DOI: 10.29007/kfk9
|View full text |Cite
|
Sign up to set email alerts
|

ARCH-COMP21 Category Report: Artificial Intelligence and Neural Network Control Systems (AINNCS) for Continuous and Hybrid Systems Plants

Abstract: This report presents the results of a friendly competition for formal verification of continuous and hybrid systems with artificial intelligence (AI) components. Specifically, machine learning (ML) components in cyber-physical systems (CPS), such as feedforward neural networks used as feedback controllers in closed-loop systems are considered, which is a class of systems classically known as intelligent control systems, or in more modern and specific terms, neural network control systems (NNCS). We more broadl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…We consider the benchmark problems used in the competition on NNCS at ARCH-COMP 2021 (Johnson et al 2021). In total there are seven problems with various features.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We consider the benchmark problems used in the competition on NNCS at ARCH-COMP 2021 (Johnson et al 2021). In total there are seven problems with various features.…”
Section: Discussionmentioning
confidence: 99%
“…We also compare to the result of NNV (Tran et al 2020b), which uses a black-box reachability method for the plant and hence loses many dependencies. In (Johnson et al 2021) the authors reported that their tool runs out of memory before the analysis finishes. The plot in Figure 5 contains intermediate results, which show that the precision declines quickly.…”
Section: Case Study: Unicycle Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Verification of the Closed-loop ACAS Xu System. Existing works have verified NNCS with a single neural network controller on a small set of initial states [15]. The closed-loop ACAS Xu system involves switching between multiple neural networks and has a large set of initial states, creating a unique challenge for verification.…”
Section: Related Workmentioning
confidence: 99%